Capturing Solutions for Learning and Scaling Up : Documenting Operational Experiences for Organizational Learning and Knowledge Sharing - Janus, Steffen Soulejman (Washington, D.C.: World Bank, 2017)
Is your organization missing important lessons from its operational experiences? This step-by-step guide shows you how to systematically capture such knowledge and use it to inform decision making, support professional learning, and scale up successes. The captured lessons--knowledge assets, the central element needed for learning--are consistently formatted documents that use operational experience to answer a specific question or challenge. The guide describes how to create and use knowledge assets in five steps: (1) identify important lessons learned by participants, (2) capture those lessons with text or multimedia documents, (3) confirm their validity, (4) prepare them for dissemination, and (5) use them for sharing, replication, and scaling up. Included tools, templates, and checklists help you accomplish each step.